Disrupting monolingual practices: The role of multilingualism as a pedagogy of possibility in Writing Centres - Namakula, Halima; Kimani, Wacango; Kadenge, Emure (Critical Studies in Teaching and Learning, 2025)
Monolingual practices that dominate university spaces can contribute to othering, resulting in the marginalisation and exclusion of students who are less competent in the dominant discourse. These limitations must be addressed to create a more inclusive learning space that accommodates all students regardless of their social, economic, educational, and linguistic backgrounds. This paper explores how peer tutors in writing centre leverage their South African indigenous language repertoire to help students access disciplinary content knowledge and improve their academic writing practices. This paper discusses the findings from two focus group discussions with peer tutors at the Wits School of Education Writing Centre (WSoE WC). We explore how peer tutors’ integration of multilingualism during writing consultations can inform a new writing centre pedagogy. We also leveraged the principles of wayfinding to navigate and orient peer tutors within a complex university space, which challenges the university’s stated educational transformation with a concrete proposition. Data analysis shows how peer tutors and students collaboratively explore and map out academic writing using familiar languages to navigate the rigid structure of academic writing in a manner that respects and incorporates students’ linguistic backgrounds. Through wayfinding, peer tutors disrupt monolingual practices and by doing so, increase student participation and chances of success in higher education. Writing centres, as wayfinding spaces, are instrumental in championing the adoption of multilingual pedagogies, thus disrupting dominant monolingual practices in higher education.